THE DEVELOPMENT OF THE "ULTACO" GAME MEDIA ON MATHEMATICS LEARNING CONTENT FOR BUILDING SPACE SURFACE AREA IN CLASS V ELEMENTARY SCHOOL STUDENTS - Siti Khoirurosidah (Jurnal JPSD (Jurnal Pendidikan Sekolah Dasar), 2021)
This development research aims to produce an Ultaco game media that is suitable for use in mathematics learning on the surface area of geometric shapes for fifth-grade elementary school students. The use of media is very necessary for learning mathematics because it helps students to understand the material well, does not saturate, can increase student activity and interest during learning. The product feasibility test is based on the results of the assessments of material experts, media experts, fifth-grade teachers and fifth-grade elementary school students as test subjects. The results of research and development of Ultaco game media can be concluded as follows: (1) The results of the assessment of material experts get a percentage of 79 .4% is included in the appropriate category, (2) the media expert's assessment gets a percentage of 95% including the very feasible category, (3) the assessment from the fifth-grade teacher gets a percentage of 85.3% including the very feasible category. Meanwhile, from users, Ultaco game media obtained a percentage of 79.4%, so that it can be categorized as feasible and interesting to use as learning media